Narrating the closet : an autoethnography of same-sex attraction - Adams, Tony E. (Writing lives--ethnographic narratives., 2011)
Motivated by the death of his partner, Adams seeks to redefine the closet as a relational construct between all people and all sexualities. The closet is explored at each stage--entering it, inhabiting it, and coming out of it--and strategies are offered for reframing difficult closet experiences. Adams makes use of interviews, personal narratives, and autoethnography to analyze lived, relational experiences of sexuality. This is a must have for scholars and students of gender studies, qualitative research, and for any reader who has felt the closet's reach.